Trends and factors associated with advanced maternal age in Brazil (Research, Society and Development, 2025)
Considering the social, economic, and public health relevance of advanced maternal age (AMA), this study aimed to examine temporal and regional patterns and the impact of socioeconomic factors (education, marital status, income, and health service access) on birth rates in Brazil. A cross-sectional observational analytical approach was used with data from DATASUS and IBGE (2000–2019). Descriptive and statistical analyses of demographic and socioeconomic variables were performed. The results show a rising trend of AMA in Brazil, with maternal education level and marital status significantly associated with this increase. Most women received excellent prenatal care, although little information is available to assess the quality of this care in most cases. Annual GDP per capita was highly correlated with childbirth to women with AMA. Finally, the number of deaths of women with late pregnancies varied greatly between Brazilian regions, being highest in the Southeast and Northeast. These findings emphasize the need for health policies targeting women of late reproductive age, ensuring access to quality care. Understanding the dynamics of late motherhood is vital for shaping effective reproductive health and family planning strategies that address regional and socioeconomic disparities.